Korelasi Tingkat Layanan Jalan (LoS) Terhadap Perubahan Morfologi dan Anatomi Thalus Lichen dalam Kota Surakarta - Tiyas, Diyah Irfin Wahyuning; Mahajoeno, Edwi; Sunarto, Sunarto (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the morphological and anatomical description of lichen thalus growing in urban areas. Sampling using exploration method (Cruise Method) and lichen thalus sampling technique is done by Purposive Sampling. Lichen thalus sample preparation was done by Embedding method. The results of this study indicate that (1) The life of lichen in urban friends is influenced by several factors including temperature, humidity and air pollutants that correlate with the LoS index value in Surakarta City. (2) Two species were found, Parmelia sp and Dirinaria sp that have different morphology and anatomy, which is caused by the characteristics of lichen substrate and air quality in the area. (3) Dirinaria sp species found in all study sites proved that the species is tolerant to environmental stress and is a taxon that characterizes urban areas. (4) The level of LoS index value in Surakarta City is also one of the factors that cause changes in the anatomical structure of the lichen thalus, namely the upper cortex layer. Thus, the higher the LoS index value in a road section, the thicker the size of the cortex thickness of the lichen thalus growing on the substrate in Surakarta City.